Cellulose nanofibrils-reduced graphene oxide xerogels and cryogels for dielectric and electrochemical storage applications. (4th July 2018) - Pottathara, Yasir Beeran; Bobnar, Vid; Finšgar, Matjaž; Grohens, Yves; Thomas, Sabu; Kokol, Vanja
Abstract: The effect of structure (density and porosity) and composition (ratio) of composites prepared from cellulose nanofibrils (CNF) and reduced graphene oxide (RGO) as film-like xerogels and porous cryogels, respectively, were investigated related to their dielectric performance and electrochemical storage abilities. A very small content (5 wt%) of RGO incorporated xerogelic film of a denser and layered structure shows relatively high dielectric constant of ∼85 and ∼164 and an ac electrical conductivity of 0.0028 S/m 2 and 0.0072 S/m 2 at 270 K and 370 K, respectively, at a high frequency of 1 MHz showing their suitability for high temperature dielectric storage applications. On the other hand, a high specific capacitance of ∼460 F/g and electrochemical resistance of 12–15 Ω cm 2 was observed for well-aligned and longitudinal-oriented micro-porous cryogel, indicate on its suitability as electrodes for electrochemical storage devices. Graphical abstract: Image 1 Highlights: CNF-RGO composites of different density and porosity (size and orientation) are prepared. Dielectric properties are investigated at highest frequency of 1 MHz. Denser and layer-structured film gave temperature dependent dielectric properties. Aligned micro-porous structure gave high specific capacitance and lower electrochemical resistance.